Coverage of large soft tissue defects of the lower limb and foot with superficial inferior epigastric artery flap - Liu, Dong; Xie, Xingwen; Chu, Ping An; Zhou, Xin; Luo, Lin; Li, Ning (Frontiers in Surgery, 2024)
BackgroundLarge soft tissue defects of the lower limb and foot are common occurrence in clinical practice and a considerable number of flaps have been used to treat them. However, there have been few reports using the superficial inferior epigastric artery (SIEA) flap. This review aims to present the experience of using the SIEA flaps for the repair of large soft tissue defects of the lower limb and foot.MethodsA retrospective review of data from 11 patients who underwent coverage of lower limb and foot defects exceeding 120 cm2 (15 × 9 cm) using SIEA flaps from March 2018 to July 2022 were retrospectively reviewed. The average size of the defects was 18 × 11 cm2 (range 15 × 9 cm2–32 × 16 cm2). Flap survival rates, surgical complications and overall long-term outcomes were recorded.ResultsAll 11 flaps survived. One flap was partially necrotic at the edge and healed after several changes of dressing. Additionally, one flap presented with mild venous congestion. The mean follow-up period was 18 months (ranging from 12 to 30 months). The mean size of the flaps was 20 × 12 cm2 (range 17 × 9 cm2–34 × 18 cm2). The flaps were observed to be aesthetically pleasing and exhibited a well-defined texture. The donor wounds were successfully closed primarily, with only linear scarring remaining.ConclusionsThe SIEA flap is characterised by concealed donor area, superficial vascular location, easy access and primary closure, which results in favourable aesthetic outcomes. It is an appropriate choice for the repair of large soft tissue defects of the lower limb and foot.